2003
DOI: 10.1002/ajpa.10233
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biological diversity through analysis of discrete cranial traits

Abstract: In the present study, the frequency distributions of 20 discrete cranial traits in 70 major human populations from around the world were analyzed. The principal-coordinate and neighbor-joining analyses of Smith's mean measure of divergence (MMD), based on trait frequencies, indicate that 1) the clustering pattern is similar to those based on classic genetic markers, DNA polymorphisms, and craniometrics; 2) significant interregional separation and intraregional diversity are present in Subsaharan Africans; 3) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 54 publications
7
96
1
13
Order By: Relevance
“…The sample names and sizes with the brief information used in this study for the second dataset are presented in Table 2. The information for these samples is also given elsewhere (Hanihara and Ishida, 2001a, b, c, d, e;Hanihara et al, 2003). The Jomon sample included in the first dataset is added to the second dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The sample names and sizes with the brief information used in this study for the second dataset are presented in Table 2. The information for these samples is also given elsewhere (Hanihara and Ishida, 2001a, b, c, d, e;Hanihara et al, 2003). The Jomon sample included in the first dataset is added to the second dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The first author and co-workers have investigated the migration and differentiation patterns of the northeast Asian populations from analyses of craniometric and nonmetric traits (Ishida, 1990(Ishida, , 1992(Ishida, , 1993(Ishida, , 1994(Ishida, , 1995(Ishida, , 1996Ishida and Dodo, 1996;Hanihara et al, 2003;Komesu et al, 2008); however, most of these phenotypic variations were analyzed by classical multivariate methods such as the Mahalanobis' generalized distance analysis using only male series.…”
Section: Introductionmentioning
confidence: 99%
“…Ossenberg (1994) and Hanihara et al (2003) demonstrated that nonmetric cranial variation, when considered as a whole, varies across regions and periods in a manner matching neutral expectations. Such findings may allow us to fruitfully discuss a plausible population history for northern Vietnam.…”
Section: Discussionmentioning
confidence: 98%
“…Cranial nonmetric traits have been widely accepted to be effective for reconstructing population histories, not only within limited geographic regions but also globally Ossenberg, 1994;Dodo and Kawakubo, 2002;Hanihara et al, 2003;Dodo and Sawada, 2010). The occurrences of cranial nonmetric traits were compared between the temporally disparate skeletal sequences discussed above for the Hoabinhian, Pre-Pottery Neolithic (PPNC, essentially Da But series), Neolithic Man Bac, and Metal period assemblages available for study in northern Vietnam, to test the validity of two-layer hypothesis as a model for understanding the population history of Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%